My Muslim friend = Ang kaibigan kong Muslim - Ordinario-Floresta, Mary Ann (ABC Educational Development Center, 2007)
"This is a true story of a touching friendship between a Muslim and a Christian girl in Mindanao. They were the best friends since childhood. They sincerely cared for the well-being of each other. They proved that both cultures could be together in peace and unity because they respected their difference in ethnicity and religion. They valued their friendship more than the opinion of other’s beliefs and ideologies in this world."